Hijaukan Bumi dengan Iman: Peran Pendidikan Agama Islam dalam Aksi Nyata Pelestarian Lingkungan - Bary, Akmal; Firmansyah, Mohammad; Suratin, Sonia Isna; Arrazaq, Zaki; Istiqomah, Febriana (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
The purpose of this article is to explore the role of Islamic Religious Education in encouraging real action for environmental conservation, with a focus on efforts to green the earth based on faith values. The research method used is a literature study, which involves the analysis of library sources to understand the concepts and principles of Islamic teachings related to the environment and their application in education. The results of the study indicate that Islamic Religious Education has significant potential in building ecological awareness and responsible behavior towards the environment through the internalization of Islamic values. Islamic teachings emphasize the harmonious relationship between humans and nature, responsible resource management, and the importance of preserving the earth as a divine mandate. Implications for the future are the need to develop a more integrative and contextual Islamic Religious Education curriculum and learning methods, which connect religious values ??with global environmental issues. In addition, this study encourages the active involvement of Islamic educational institutions, religious figures, and Muslim communities in the environmental conservation movement, as well as cross-sector collaboration to achieve sustainable development goals. Thus, Islamic Religious Education can be a transformative force in realizing a greener and more sustainable earth based on faith principles.